2005
DOI: 10.1002/ange.200502018
|View full text |Cite
|
Sign up to set email alerts
|

Deracemization of Quaternary Stereocenters by Pd‐Catalyzed Enantioconvergent Decarboxylative Allylation of Racemic β‐Ketoesters

Abstract: Enantioconvergent catalysis is a powerful synthetic method that converts a racemic stereogenic substrate into an enantiomerically enriched product with a theoretical yield of 100 % in a single operation.[1] Conceptually, a catalytic system for such a reaction must achieve a stereomutation [2] or stereoablation [3,4] of the substrate (or an intermediate), followed by an enantioselective conversion into product (Figure 1, compare pathways I and II). A number of catalytic processes of this type have been develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
11

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 27 publications
0
66
0
11
Order By: Relevance
“…With the requisite isoprenyl fragment in place, the application of the group's previously developed Pd-catalyzed asymmetric allylic alkylation methodology [47, 48] with Pd 2 (pmdba) 3 and ( S )- t -Bu-PHOX ( 101 ) smoothly provided enantioenriched vinylogous ester 102 in 91% yield and 95% ee. Conversion of the compound to acylcyclopentene 104 was achieved by employing a recently developed two-carbon ring contraction sequence.…”
Section: Synthetic Studies Toward the Presilphiperfolanol Natural mentioning
confidence: 99%
“…With the requisite isoprenyl fragment in place, the application of the group's previously developed Pd-catalyzed asymmetric allylic alkylation methodology [47, 48] with Pd 2 (pmdba) 3 and ( S )- t -Bu-PHOX ( 101 ) smoothly provided enantioenriched vinylogous ester 102 in 91% yield and 95% ee. Conversion of the compound to acylcyclopentene 104 was achieved by employing a recently developed two-carbon ring contraction sequence.…”
Section: Synthetic Studies Toward the Presilphiperfolanol Natural mentioning
confidence: 99%
“…In the earliest report by Stoltz in 2004, numerous chiral bidentate ligands were screened for their ability to promote high asymmetric induction in reactions with allyl enol carbonate and silyl enol ether substrates (Scheme 4). [17a] Ultimately, it was found that treatment of these substrates with the combination of ( S )- t Bu-PHOX ( 13 , Figure 2) and [Pd 2 (dba) 3 ] provided the highest degrees of enantioenrichment in the α-quaternary ketone products. Other P , N - and P , P -chelating ligands were investigated, but they proved to be less effective under the optimized conditions.…”
Section: Reaction Design and Mechanistic Considerationsmentioning
confidence: 99%
“…[17b,17c] The starting materials are racemates, so the destruction and reconstruction of stereochemical information through the intermediacy of a prochiral enolate must take place in order for these compounds to form asymmetric alkylation products in what has been termed a stereoablative process. [19] Despite this key mechanistic difference, these substrates demonstrated yields and levels of asymmetric induction similar to those obtained with the silyl enol ethers and enol carbonates.…”
Section: Reaction Design and Mechanistic Considerationsmentioning
confidence: 99%
See 2 more Smart Citations